Green Synthesis of Gold Nanoparticles using Pimenta dioica Leaves Aqueous Extract and Their Application as Photocatalyst, Antioxidant, and Antibacterial Agents - Adewale Fadaka; Olukemi Aluko; Saartjie Awawu; Karim Theledi (Pandawa Institute, 2021)
Green synthesis of gold nanoparticles (AuNPs) is of particular interest due to their catalytic, antioxidant, and antibacterial properties. In this study, the aqueous extract of Pimenta dioica leaves was used to synthesize AuNPs and the effective parameters were investigated. The prepared AuNPs were characterized by various techniques including UV–Vis absorption spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM), and X-ray diffractometer (XRD). The reduction and stabilization effect of the plant extract to fabricate AuNPs were explained by FTIR analysis. TEM imaging confirmed the formation of spherical-shaped AuNPs. The catalytic activity of synthesized nanoparticles was evaluated in the degradation of a Methylene Blue dye in the presence of NaBH4 as reducing agent and achieved after only two minutes. The AuNPs provided high antioxidant ability. In addition, the synthesized AuNPs showed a significant inhibitory effect against both gram-positive and gram-negative bacteria, where the zone of inhibition of 4 and 9 mm were obtained for synthesized AuNPs against S. aureus and E. coli, respectively.